Crystal structure and physical properties of Cr and Mn oxides with 3d3 electronic configuration and a K2NiF4-type structure. Issue 14 (2nd March 2015) - Kao, Ting-Hui; Sakurai, Hiroya; Kolodiazhnyi, Taras; Suzuki, Yutaro; Okabe, Momoko; Asaka, Toru; Fukuda, Koichiro; Okubo, Susumu; Ikeda, Shohei; Hara, Shigeo; Sakurai, Takahiro; Ohta, Hitoshi; et al.
Abstract : YSrCrO4 is first synthesized. The magnetic and dielectric properties of YCaCrO4, LaSrCrO4 and A2 MnO4 (A = Sr and Ca) are investigated together with YSrCrO4 . Abstract : YSrCrO4 is first synthesized and found to be a hettotype of the K2 NiF4 structure, although the combination of Y and Sr ions in K2 NiF4 -type oxides is very rare. The space group of the compound is determined to be orthorhombic Pccn by the electron diffraction and the powder X-ray diffraction. Magnetic and dielectric properties of the compound, together with LaSrCrO4, YCaCrO4 and A2 MnO4 (A = Sr and Ca), are investigated. YSrCrO4 shows two-dimensional (2D) spin correlations and a canted antiferromagnetic (AF) ordering. With increasing distortion of the crystal structure, 2D spin correlations and the AF transition temperature decrease, while spontaneous magnetization increases. From the multi-frequency electron spin resonance (ESR) measurements, the g -values of the paramagnetic state are estimated to be 1.976, 1.978 and 1.976 for YSrCrO4, LaSrCrO4 and YCaCrO4, respectively. Evidence of AF ordering of the Cr oxides is obtained microscopically from ESR. The dielectric measurements suggest the existence of in-gap states, while no magneto-dielectric coupling was observed in the above compounds.